Uv light-cured fluorosilicon resin, preparation method thereof and self-cleaning coating

CN122917316APending Publication Date: 2026-10-16HUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611376233.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,现有UV固化有机硅体系多采用铂金催化或过氧化物引发,成本较高,且难以同时满足高硬度(≥6H)和高附着力(0级)的要求

Benefits of technology

[0025]1. This invention uses hydrolysis-condensation polymerization with MM, DEDMS, KH-570 and 17F as raw materials and hydrochloric acid as a catalyst to synthesize a UV-curable fluorosilicone resin containing both acrylate photosensitive groups and fluorinated side chains. The process is simple, the raw materials are widely available, the cost is controllable, and industrial production can be realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917316A_ABST
    Figure CN122917316A_ABST
Patent Text Reader

Abstract

The application discloses a UV light-cured fluorosilicone resin, a preparation method thereof and a self-cleaning coating, and aims to provide the fluorosilicone resin which has the advantages of simple preparation method, fast cross-linking and curing under ultraviolet light irradiation, colorless transparency before curing, high hardness, high adhesion, good hydrophobicity, excellent thermal stability, short curing time, low energy consumption and green environmental protection, and the like, and belongs to the technical field of coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of coating technology, specifically a UV-curable fluorosilicone resin, its preparation method, and a self-cleaning coating. Background Technology

[0002] Self-cleaning coatings are a type of functional interface with special surface chemical composition and microstructure design. They achieve excellent hydrophobicity through high contact angles (CAs), thereby minimizing surface wetting and moisture absorption. They can prevent pollutants from adhering or quickly desorbing under external environmental conditions (such as rain and wind), thus achieving self-cleaning. They are indispensable in industries such as automotive, aerospace, shipbuilding, construction, oil and gas.

[0003] Currently, research on self-cleaning coatings mainly focuses on two major directions: one is self-cleaning surfaces based on surface wettability regulation, including hydrophobic and hydrophilic types. Hydrophobic coatings utilize the "lotus effect," where water droplets roll on the surface and carry away dust when the contact angle exceeds 150° and the contact angle hysteresis is less than 5°. Superhydrophilic coatings, on the other hand, allow water droplets to spread rapidly and form a continuous water film, encapsulating and carrying away pollutants. The second is self-cleaning surfaces based on photocatalysis. Photocatalytic coatings utilize photocatalysts such as TiO2 to generate strong oxidizing substances under light to degrade pollutants.

[0004] Organosilicon resins have Si-O bonds as their main chain backbone. The high bond energy of Si-O bonds endows them with excellent thermal stability and mechanical flexibility; however, their solvent resistance is poor. Fluorosilicone resins are polymer materials that introduce fluorine-containing groups into the organosilicon backbone, and at the same time combine the characteristics of organosilicon resins and organofluorine resins, thereby overcoming their poor solvent resistance. However, traditional fluorosilicone resin coatings often cannot achieve a balance between hardness, adhesion and hydrophobicity. Although high fluorine content can improve hydrophobicity, it can easily lead to a decrease in coating transparency and a decrease in adhesion.

[0005] Furthermore, current traditional fluorosilicone resin coatings mainly employ high-temperature thermosetting processes, which involve high curing temperatures (typically 150~180℃), high energy consumption, and slow curing rates, making continuous production impossible. Moreover, high-temperature curing is unsuitable for heat-sensitive substrates. This makes it difficult to meet the demands of large-scale industrial applications.

[0006] UV-curable acrylate-modified fluorosilicone resins involve modifying fluorosilicone resin molecules by chemically grafting UV-curable acrylate groups onto the siloxane backbone or side chains. Under ultraviolet light and photoinitiators, a free radical polymerization reaction occurs, rapidly cross-linking and curing to form a three-dimensional network polymer coating. This coating combines the excellent hydrophobicity, oleophobicity, weather resistance, and low surface energy of fluorosilicone resins with the rapid UV curing, high hardness, and high adhesion of acrylate systems. However, existing UV-curable silicone systems often use platinum catalysis or peroxide initiation, which is costly and makes it difficult to simultaneously meet the requirements of high hardness (≥6H) and high adhesion (Grade 0).

[0007] Therefore, it is necessary to propose a UV-curable fluorosilicone resin to solve the technical problems of high curing temperature and high energy consumption of traditional fluorosilicone resins, as well as the difficulty of achieving high hardness, high adhesion and excellent hydrophobicity of existing UV-curable fluorosilicone resins at the same time, so as to provide a feasible technical solution for large-scale industrial production of self-cleaning coatings. Summary of the Invention

[0008] To address the aforementioned shortcomings, the first objective of this invention is to provide a UV-curable fluorosilicone resin and its preparation method. This resin preparation method is simple, and it can be rapidly crosslinked and cured under ultraviolet irradiation, and is colorless and transparent before curing.

[0009] The second objective of this invention is to provide a UV-curable fluorosilicone resin self-cleaning coating that combines high hardness, high adhesion, good hydrophobicity, and excellent thermal stability, while also having a short curing time, low energy consumption, and being environmentally friendly.

[0010] Therefore, the first technical solution provided by this invention is as follows:

[0011] A UV-curable fluorosilicone resin, by weight, is prepared from the following raw materials: 10-16 parts hexamethyldisiloxane; 18-19 parts dimethyldiethoxysilane; 46-47 parts silane coupling agent; 53-89 parts perfluorodecyltrimethoxysilane; 2.5-3.3 parts hydrochloric acid; and 17-20 parts deionized water.

[0012] Furthermore, in the aforementioned UV-curable fluorosilicone resin, the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane.

[0013] Another technical solution of the present invention is to provide a method for preparing the above-mentioned UV-curable fluorosilicone resin, which includes the following steps in sequence:

[0014] S1: Weigh out each component;

[0015] S2: At room temperature, add the hexamethyldisiloxane, dimethyldiethoxysilane, silane coupling agent and perfluorodecyltrimethoxysilane weighed in step S1 into the reaction flask and start stirring. While stirring, slowly add the mixture of hydrochloric acid and deionized water dropwise. During the dropwise addition, control the temperature inside the flask to be below 40°C. After the dropwise addition is complete, start heating until the temperature inside the flask reaches 70°C and then keep the reaction at this temperature for 3 to 3.5 hours.

[0016] S3: After the heat preservation is completed, the liquid is rotary evaporated at 95~100℃ and -0.095MPa until the liquid stops boiling and no low-boiling substances are distilled out in the condenser, resulting in a colorless, transparent, viscous liquid.

[0017] S4: Cool down to below 40°C, add sodium carbonate and stir for at least 30 minutes, then filter out the powder to obtain UV-curable fluorosilicone resin.

[0018] Another technical solution of the present invention is a UV-curable self-cleaning coating, which is made by compounding the above-mentioned UV-curable fluorosilicone resin with an active diluent, adding a photoinitiator, coating it on the surface of a substrate, and curing it under ultraviolet light for 30s to 120s.

[0019] Furthermore, in the aforementioned UV-curable self-cleaning coating, the active diluent is composed of isoborneol acrylate and glycidyl methacrylate in a molar ratio of 4:1.

[0020] Furthermore, in the aforementioned UV-curable self-cleaning coating, the molar ratio of the UV-curable fluorosilicone resin, isoborneol acrylate, and glycidyl methacrylate is 2:4:1.

[0021] Furthermore, in the aforementioned UV-curable self-cleaning coating, the photoinitiator is one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylpropanone.

[0022] Furthermore, in the aforementioned UV-curable self-cleaning coating, the amount of photoinitiator added is 1% to 3% of the total mass of the UV-curable fluorosilicone resin.

[0023] Furthermore, in the aforementioned UV-curable self-cleaning coating, the thickness of the UV-curable self-cleaning coating is controlled to be 20~50μm.

[0024] Compared with the prior art, the technical solution provided in this application has the following technical advantages:

[0025] 1. This invention uses hydrolysis-condensation polymerization with MM, DEDMS, KH-570 and 17F as raw materials and hydrochloric acid as a catalyst to synthesize a UV-curable fluorosilicone resin containing both acrylate photosensitive groups and fluorinated side chains. The process is simple, the raw materials are widely available, the cost is controllable, and industrial production can be realized.

[0026] 2. The fluorosilicone resin prepared by this invention has both good fluidity and a suitable molecular weight distribution. It is a colorless, transparent, viscous liquid with a dynamic viscosity of 600~2500 mPa·s at 25℃, a refractive index of 1.39-1.41 at 25℃, a visible light transmittance of ≥95%, and a high transmittance at 365nm, which meets the application requirements of optical coatings and is suitable for transparent self-cleaning applications such as solar panel covers and optical lenses.

[0027] 3. The self-cleaning coating prepared in this application adopts a dual active diluent system of IBOA and GMA, which effectively solves the problems of poor adhesion when there is no GMA and decreased hardness when there is excessive GMA. The initial adhesion of the coating in all application examples of this application reaches level 0, which solves the contradiction between hardness and adhesion.

[0028] 4. The self-cleaning coating prepared in this application is colorless, transparent, and defect-free after curing (it is translucent to cloudy with high fluorine content). It has a pencil hardness of 6H and a water contact angle of 103.7°, exhibiting both high hardness, high adhesion, and good hydrophobic properties. Furthermore, it demonstrates excellent thermal stability, with a thermal decomposition temperature (T0) of 5.0% mass loss. 5% ≥118.0℃, glass transition temperature (T) g ≥70.71℃. The coating maintains structural stability below 300℃, meeting the temperature resistance requirements of most outdoor applications; it has excellent acid and alkali resistance, and its adhesion rating remains at level 1 even in acidic / alkaline environments.

[0029] 5. The self-cleaning coating prepared in this application adopts UV curing technology, which can complete curing within 30 to 120 seconds. The energy consumption is only 1 / 5 to 1 / 10 of that of thermal vulcanization molding. It is green and environmentally friendly, and can realize continuous production. It has wide application value in the fields of automotive windshields, architectural glass, solar panels, electronic device screens, etc. Attached Figure Description

[0030] Figure 1 These are the infrared spectra of FSR resins with different R / Si values;

[0031] Figure 2 These are FSR resins with different R / Si values. 1 H NMR spectrum;

[0032] Figure 3These are the UV-Vis transmittance curves of FSR resins with different R / Si values;

[0033] Figure 4 These are TGA test curves for coatings with different formulations;

[0034] Figure 5 These are the DSC test curves for coatings with different formulations;

[0035] Figure 6 These are adhesion (cross-cut adhesion test) graphs for coatings with different formulations;

[0036] Figure 7 These are test charts of water contact angles for coatings with different formulations;

[0037] Figure 8 These are test charts showing the alkali resistance adhesion of coatings with different formulations;

[0038] Figure 9 These are test charts showing the acid resistance and adhesion of coatings with different formulations. Detailed Implementation

[0039] The technical solution of the present invention will be clearly and completely described below with reference to embodiments thereof. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides an FSR-1 fluorosilicone resin, which is prepared by the following steps: 10.15g of hexamethyldisiloxane (MM), 18.54g of dimethyldiethoxysilane (DEDMS), 46.57g of γ-methacryloyloxypropyltrimethoxysilane (KH-570), and 53.28g of perfluorodecyltrimethoxysilane (17F) are added to a four-necked flask equipped with a mechanical stirrer, a constant pressure funnel, a condenser, and a thermometer, and stirring is started. Subsequently, while stirring, a mixture of hydrochloric acid (2.57g) and deionized water (19.72g) is poured into the constant pressure funnel and slowly dripped into the four-necked flask, controlling the temperature inside the flask to be below 40°C during the dripping process. After the dripping is completed, the temperature is raised until the temperature inside the flask reaches 70°C, and then the reaction is maintained at this temperature for 3 hours. After the heat preservation period, the liquid was rotary evaporated at 95~100℃ and -0.095MPa until the liquid stopped boiling and no low-boiling substances distilled out in the condenser, resulting in a colorless, transparent, high-viscosity liquid. The vacuum distillation apparatus was then removed, the flask was tightly sealed, and the temperature was lowered to below 40℃. Sodium carbonate was added and stirred for at least 30 minutes. Finally, the powder was filtered out using a positive pressure filter, yielding a colorless, transparent, viscous liquid, which is fluorosilicone resin FSR-1 (R / Si=1.71).

[0042] Example 2

[0043] This embodiment provides an FSR-2 fluorosilicone resin, which is prepared by the following steps: 16.24 g of hexamethyldisiloxane (MM), 18.54 g of dimethyldiethoxysilane (DEDMS), 46.57 g of γ-methacryloyloxypropyltrimethoxysilane (KH-570), and 71.04 g of perfluorodecyltrimethoxysilane (17F) are added to a four-necked flask equipped with a mechanical stirrer, a constant pressure funnel, a condenser, and a thermometer, and stirring is started. Subsequently, while stirring, a mixture of 3.05 g of hydrochloric acid and 18.52 g of deionized water is loaded into the constant pressure funnel and slowly added dropwise to the four-necked flask, controlling the temperature inside the flask to be below 40°C during the dropwise addition. After the addition is complete, the temperature is raised until the temperature inside the flask reaches 70°C, and then the reaction is maintained at this temperature for 3 hours. After the heat preservation period, the liquid was rotary evaporated at 95~100℃ and -0.095MPa until the liquid stopped boiling and no low-boiling substances distilled out in the condenser, resulting in a colorless, transparent, high-viscosity liquid. The vacuum distillation apparatus was then removed, the flask was tightly sealed, and the temperature was lowered to below 40℃. Sodium carbonate was added and stirred for at least 30 minutes. Finally, the powder was filtered out using a positive pressure filter, yielding a colorless, transparent, viscous liquid, which is the fluorosilicone resin FSR-2 (R / Si=1.67).

[0044] Example 3

[0045] This embodiment provides an FSR-3 fluorosilicone resin, which is prepared by the following steps: 10.15g of hexamethyldisiloxane (MM), 18.54g of dimethyldiethoxysilane (DEDMS), 46.57g of γ-methacryloyloxypropyltrimethoxysilane (KH-570), and 88.80g of perfluorodecyltrimethoxysilane (17F) are added to a four-necked flask equipped with a mechanical stirrer, a constant pressure funnel, a condenser, and a thermometer, and stirring is started. Subsequently, while stirring, a mixture of hydrochloric acid (3.28g) and deionized water (17.60g) is poured into the constant pressure funnel and slowly dripped into the four-necked flask, controlling the temperature inside the flask to be below 40°C during the dripping process. After the dripping is completed, the temperature is raised until the temperature inside the flask reaches 70°C, and then the reaction is maintained at this temperature for 3 hours. After the heat preservation period, the liquid was rotary evaporated at 95~100℃ and -0.095MPa until the liquid stopped boiling and no low-boiling substances distilled out in the condenser, resulting in a colorless, transparent, high-viscosity liquid. The vacuum distillation apparatus was then removed, the flask was tightly sealed, and the temperature was lowered to below 40℃. Sodium carbonate was added and stirred for at least 30 minutes. Finally, the powder was filtered out using a positive pressure filter, yielding a colorless, transparent, viscous liquid, which is the fluorosilicone resin FSR-3 (R / Si=1.63).

[0046] I. The resins prepared in Examples 1-3 were subjected to performance tests, and the test methods are as follows:

[0047] (1) Fourier transform infrared spectroscopy (FTIR)

[0048] The wavelength range was 4000 ~ 500 cm⁻¹ using a Bruker ALPHA-11 Fourier transform infrared spectrometer (Germany) and the KBr pellet method. -1 The resolution is 4 cm. -1 It was obtained by scanning 32 times.

[0049] (2) Nuclear magnetic resonance (NMR) 1 H NMR / 13 (C NMR)

[0050] 1 1H NMR: The structure of the UV-curable fluorosilicone resin was determined at room temperature using an AVANCE NEO 600MHz instrument from Bruker, Switzerland, with deuterated chloroform (CDCl3) as solvent and 1,4-dioxane as internal standard.

[0051] 13 C10 NMR: At room temperature, using a Bruker AVANCE NEO 600MHz nuclear magnetic resonance spectrometer (Switzerland) with deuterated chloroform (CDCl3) as solvent, the values ​​of UV-cured fluorosilicone resin before and after the reaction were determined. 13 Changes in C NMR spectra.

[0052] (3) Ultraviolet-Vis transmission spectrum (UV-Vis)

[0053] Using air as the reference medium at room temperature, the transmittance of the sample was measured in the 300-800 nm wavelength range using a Shimadzu UV-2900i UV-Vis spectrophotometer, with the scan step size set to 1.0 nm.

[0054] (4) Density

[0055] According to GB / T 6750-2007 standard, the density of liquid samples was determined using a density cup at 25℃ using an AUY 120 analytical balance from Shimadzu Corporation of Japan.

[0056] (5) Viscosity

[0057] According to GB / T 10247-2008 standard, the viscosity of liquid samples was measured using the NTV-S1 digital rotational viscometer from Shanghai Nirun Intelligent Technology Co., Ltd.

[0058] (6) Refractive index

[0059] According to the GB / T 6448-2008 standard, the 2WAJ monocular Abbe refractometer from Shanghai Optical Instrument Factory was used for testing. Each sample was measured in parallel three times, and the average value was taken.

[0060] Characterization results:

[0061] FT-IR test results ( Figure 1 Display: 2960 cm -1 The absorption peak at 1720 cm⁻¹ is the CH stretching vibration absorption peak in -CH₃. -1 The absorption peak near the -COO- stretching vibration of -C=O- is 1630 cm⁻¹. -1 The vicinity is near the -C=C- stretching vibration peak, and FSR-1 / 2 / 3 is at 1720 cm⁻¹. -1 and 1630 cm -1 Clear absorption peaks were observed in the vicinity, proving that UV-curable acrylate groups were successfully introduced into the resin; 1200 cm⁻¹ -1 The absorption peak for the stretching vibration of -CF3 is near the FSR-1 / 2 / 3 at 1200 cm⁻¹. -1 Clear absorption peaks were observed in the vicinity, proving that fluorine side chains were successfully introduced into the resin; 1100 cm⁻¹ -1 The nearby Si-O-Si stretching vibration absorption peak is a characteristic peak of the silicone resin skeleton, indicating the successful synthesis of UV-curable fluorosilicone resin; the acrylate double bond at 1720 cm⁻¹... -1 There is a clear infrared absorption peak nearby, and the fluorine-containing side chain is at 1200 cm⁻¹. -1The presence of characteristic absorption peaks nearby, with stronger absorption at higher fluorine content, confirms the successful introduction of acrylate groups and fluorine-containing side chains, as well as the formation of the Si-O-Si framework.

[0062] ¹H NMR test results ( Figure 2 The following peaks are observed: 0.04–0.07 ppm represent hydrogen proton peaks on the methyl groups of MM and DEDMS; 0.59–0.64 ppm represent hydrogen proton peaks on the carbon atom of the perfluorodecyl side chain linked to silicon; 0.79 ppm represents hydrogen proton peaks on the carbon atom of KH-570 linked to silicon; 1.67–1.71 ppm represents hydrogen proton peaks on the bridged methylene group directly linked to silicon on KH-570; 1.87 ppm represents hydrogen proton peaks on the geminal methyl group of the unsaturated double bond of acrylate on KH-570; 2.07 ppm represents hydrogen proton peaks on the bridged methylene group between silicon and the perfluorocarbon chain in the perfluorodecyl group; 4.03–4.07 ppm represents hydrogen proton peaks on the carbon atom directly linked to the acrylate group on KH-570; 6.03 ppm represents hydrogen proton peaks on the carbon atom of KH-570 linked to the acrylate group; The ppm value represents the hydrogen proton peak on the carbon-carbon double bond in KH-570. The characteristic absorption peaks of hydrogen atoms of perfluorodecyl and acrylate groups were observed in all three FSR resins, indicating the successful synthesis of UV-curable fluorosilicone resins. The physical properties of the resins are shown in Table 1.

[0063] Table 1 Physical properties of FSR resins with different R / Si values

[0064] Example 1 FSR-1 (R / Si=1.71) Colorless and transparent 622 1.023 1.4023 96.9 Example 2 FSR-2 (R / Si=1.67) Colorless and transparent 1328 1.029 1.3876 96.2 Example 3 FSR-3 (R / Si=1.63) Colorless and transparent 2350 1.036 1.3932 95.1

[0065] Application Example 1

[0066] This application example provides a self-cleaning coating. The fluorosilicone resin FSR-1 prepared in Example 1 is mixed with IBOA and GMA at a mass ratio of 2:4:1. 3% (by mass) of the photoinitiator Irgacure 819 of the fluorosilicone resin FSR-1 is added. After stirring until homogeneous, vacuum degassing is performed, and the mixture is coated onto a glass substrate. The coating is applied at a wavelength of 395 nm, an irradiation energy of 300 mJ / cm², and a maximum irradiation intensity of 80 mW / cm². 2 Under these conditions, a colorless, transparent, self-cleaning coating (coating #1) was obtained by irradiating the coating with a UV curing machine for 60 seconds.

[0067] Application Example 2

[0068] This application example provides a self-cleaning coating. The fluorosilicone resin FSR-2 prepared in Example 2 is mixed with IBOA and GMA in a mass ratio of 2:4:1. 3% of the mass of the fluorosilicone resin FSR-2 photoinitiator Irgacure 819 is added. After stirring evenly, the mixture is degassed under vacuum and coated onto a glass substrate. Under conditions of wavelength 395nm, irradiation energy of 300 mJ / cm², and maximum irradiation intensity of 80 mW / cm², it is irradiated by a UV curing machine for 60s to obtain a colorless and transparent self-cleaning coating (coating 2#).

[0069] Application Example 3

[0070] This application example provides a self-cleaning coating. The fluorosilicone resin FSR-3 prepared in Example 3 is mixed with IBOA and GMA in a mass ratio of 2:4:1. 3% of the mass of the fluorosilicone resin FSR-3 is added as photoinitiator Irgacure 819. After stirring evenly, the mixture is degassed under vacuum and coated onto a glass substrate. Under conditions of wavelength 395nm, irradiation energy 300 mJ / cm², and maximum irradiation intensity 80 mW / cm², the mixture is irradiated for 60s using a UV curing machine to obtain a cloudy self-cleaning coating (coating 3#).

[0071] Comparative Example 1

[0072] The FSR-2 resin prepared in Example 2 was compounded with IBOA at a molar ratio of 1:1, and 3% by mass of the photoinitiator Irgacure 819 of the fluorosilicone resin FSR-2 was added. After stirring evenly, the mixture was degassed under vacuum and coated onto a glass substrate. Under conditions of wavelength 395nm, irradiation energy of 300 mJ / cm², and maximum irradiation intensity of 80 mW / cm², the mixture was irradiated for 60s by a UV curing machine to obtain a colorless, transparent, self-cleaning coating (coating #4).

[0073] Comparative Example 2

[0074] The FSR-2 resin prepared in Example 2 was compounded with IBOA and GMA in a molar ratio of 1:1:2. 3% (by mass) of the photoinitiator Irgacure 819 of the fluorosilicone resin FSR-2 was added and stirred until homogeneous. The mixture was then degassed under vacuum and coated onto a glass substrate. Under conditions of wavelength 395 nm, irradiation energy of 300 mJ / cm², and maximum irradiation intensity of 80 mW / cm², it was irradiated for 60 s using a UV curing machine to obtain a colorless, transparent, self-cleaning coating (coating #5).

[0075] The coating prepared in Comparative Example 2 was subjected to performance testing using the same methods as in Application Example 1. After curing, the coating exhibited excellent adhesion (grade 0), but its hardness decreased significantly (≤2H). This indicates that excessive GMA resulted in a high proportion of epoxy groups, diluting the crosslinking density of the acrylate and leading to a significant decrease in hardness.

[0076] For example 1-3, the coatings prepared in comparison example 1-2 were subjected to performance tests, and the test methods are as follows:

[0077] (1) TGA test

[0078] A Netzsch TG 209F1 thermogravimetric analyzer (Germany) was used. Samples ranging from 2.00 to 5.00 mg were weighed into ceramic crucibles at room temperature. The N2 flow rate was 20 mL / min, the test temperature range was 30–800 °C, and the heating rate was 10 °C / min. The mass change curve of the sample was recorded throughout the heating process from 30 °C to 800 °C.

[0079] (2) DSC test

[0080] A Netzsch DSC 214 Polyma differential scanning calorimeter was used. At room temperature, 5.00–10.00 mg of sample was placed in an aluminum crucible and cooled to -30°C under a flow of liquid nitrogen (N2) for 10 min. The temperature was then increased to 200°C at a rate of 5°C / min. The glass transition temperature (T0) was then determined. g ).

[0081] (3) Pencil hardness

[0082] The hardness of each formulation was tested using a BGD505 precision pencil hardness tester from BGD Precision Instruments. Five parallel tests were conducted for each formulation, and the average value was taken.

[0083] (4) Adhesion

[0084] The coating detachment in the grid was observed using the Dongguan Huaguo Precision Instruments QFH-HG600 cross-cut tester according to GB / T 9286-1998 (100-grid test).

[0085] (5) Water contact angle

[0086] The Dongguan Kezhong Precision Instruments FED-A1 contact angle measuring instrument was used, with distilled water and optical imaging to capture the droplet profile.

[0087] (6) Resistance to acids and alkalis

[0088] After soaking in sulfuric acid solution (pH=1) and sodium carbonate solution (pH=11) for 24 hours, the adhesion was measured, and the detachment of the coating in the mesh was observed and recorded.

[0089] The test results are shown in Table 2, and Figures 3-9 .

[0090] Table 2

[0091] Application Example 1 Colorless and transparent 4H 0 83.1 157.0 74.91 Application Example 2 Colorless and transparent 6H 0 101.5 118.0 70.71 Application Example 3 turbid 6H 0 103.7 180.0 76.99 Comparative Example 1 Colorless and transparent ≥6H 4 92.7° 132.6 73.65 Comparative Example 2 Colorless and transparent ≤2H 0 121.6° 92.3 67.29

[0092] Table 2 shows the experimental data analysis as follows: As the R / Si value in the fluorosilicone resin decreases, the fluorine content of the resin gradually increases, corresponding to an increase in the water contact angle of the self-cleaning coating from 83.1° to 103.7°. This indicates that the introduction of fluorine effectively improves the hydrophobicity of the coating, making it more conducive to achieving the self-cleaning function. Simultaneously, the pencil hardness of the coating also increases from 4H to 6H with increasing fluorine content, and the thermal stability gradually improves, with the 5wt% thermogravimetric temperature increasing from 157.0℃ to 180.0℃. However, excessively high fluorine content also has negative effects. When the R / Si ratio drops to 1.63, the coating becomes cloudy, and the visible light transmittance decreases to 95.1%, failing to meet the requirements of high transparency applications.

[0093] In addition, when GMA is not added to the diluent, the coating hardness can reach above 6H, but the adhesion is only level 4, and the coating is very easy to peel off. When GMA is added in excess, the coating adhesion can be stabilized at level 0, but the hardness drops to 2H and below, which cannot meet the requirements for high wear resistance. Only when IBOA and GMA are compounded in a 4:1 ratio can the coating achieve both level 0 adhesion and a pencil hardness of up to 6H, solving the problem that it is difficult to achieve both properties in traditional formulations.

[0094] Furthermore, after the coating prepared in the application example was soaked in an acidic solution with pH=1 and an alkaline solution with pH=11 for 24 hours, the adhesion did not change and remained at level 0. There was no visible coating peeling or discoloration, indicating that the UV-cured fluorosilicone self-cleaning coating prepared by the present invention has stable acid and alkali corrosion resistance and can meet the usage requirements of complex outdoor environments.

Claims

1. A UV-curable fluorosilicone resin, characterized in that, The product is prepared from the following raw materials in parts by weight: 10-16 parts hexamethyldisiloxane; 18-19 parts dimethyldiethoxysilane; 46-47 parts silane coupling agent; 53-89 parts perfluorodecyltrimethoxysilane; 2.5-3.3 parts hydrochloric acid; and 17-20 parts deionized water.

2. The UV-curable fluorosilicone resin according to claim 1, characterized in that, The silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane.

3. The method for preparing the UV-curable fluorosilicone resin according to claim 1, characterized in that, The steps are as follows: S1: Weigh each component according to the mass number described in claim 1; S2: At room temperature, add the hexamethyldisiloxane, dimethyldiethoxysilane, silane coupling agent and perfluorodecyltrimethoxysilane weighed in step S1 into the reaction flask and start stirring. While stirring, slowly add the mixture of hydrochloric acid and deionized water dropwise. During the dropwise addition, control the temperature inside the flask to be below 40°C. After the dropwise addition is complete, start heating until the temperature inside the flask reaches 70°C and then keep the reaction at this temperature for 3 to 3.5 hours. S3: After the heat preservation is completed, the liquid is rotary evaporated at 95~100℃ and -0.095MPa until the liquid stops boiling and no low-boiling substances are distilled out in the condenser, resulting in a colorless, transparent, viscous liquid. 4.S4: Cool down to below 40°C, add sodium carbonate and stir for at least 30 minutes, then filter out the powder to obtain UV-curable fluorosilicone resin.

5. A UV-curable self-cleaning coating, characterized in that, The UV-curable fluorosilicone resin of claim 1 is compounded with an active diluent, a photoinitiator is added, and the mixture is coated onto the surface of a substrate and cured under ultraviolet light for 30s to 120s.

6. The UV-curable self-cleaning coating according to claim 4, characterized in that, The active diluent is composed of isobornyl acrylate and glycidyl methacrylate in a molar ratio of 4:

1.

7. The UV-curable self-cleaning coating according to claim 4, characterized in that, The molar ratio of the UV-curable fluorosilicone resin, isobornyl acrylate, and glycidyl methacrylate is 2:4:

1.

8. The UV-curable self-cleaning coating according to claim 4, characterized in that, The photoinitiator is one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylpropanone.

9. The UV-curable self-cleaning coating according to claim 4, characterized in that, The amount of photoinitiator added is 1% to 3% of the total mass of the UV-curable fluorosilicone resin.

10. The UV-curable self-cleaning coating according to claim 4, characterized in that, The thickness of the UV-curable self-cleaning coating is controlled to be 20~50μm.